Negative electrode active material and application thereof
By using silicon-based materials modified with carbon materials and doped elements, the problem of battery performance degradation caused by volume expansion of silicon-based materials is solved, and high energy density, excellent magnification and cycling performance are achieved.
Patent Information
- Application Number
- CN202411595919.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-08
Smart Images

Figure BDA0005128130580000131
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a negative electrode active material and application thereof. Background Art
[0002] Lithium-ion batteries are now widely used in electric vehicles, hybrid electric vehicles and plug-in hybrid vehicles due to their high specific energy, long cycle life, green and safe advantages. With the rapid development of electric vehicles, people's demand for the range of lithium-ion batteries is getting higher and higher. Therefore, how to improve the capacity of lithium-ion batteries has gradually become the top priority of lithium-ion battery development.
[0003] At present, the lithium-ion batteries in the industry mainly use graphite (artificial graphite, natural graphite), and the theoretical gram capacity of graphite is 372mAh / g. The gram capacity of graphite currently produced in batches is close to the theoretical gram capacity, and the improvement of battery energy density has reached its limit. In order to further increase the capacity of lithium-ion batteries, the current focus is on developing new negative electrode active materials with high capacity characteristics, such as silicon or tin, whose theoretical capacity is at least 10 times that of graphite, and is expected to replace graphite negative electrode materials to improve the energy density of lithium-ion batteries. However, when silicon-based materials are used as negative electrode active materials, they will produce a large volume expansion during the charge and discharge process of lithium-ion batteries, which will cause the density of the negative electrode active material layer to decrease. In severe cases, peeling and fracture may even occur, which will significantly reduce the performance of lithium-ion batteries.
[0004] In order to improve the properties of silicon-based materials, various attempts have been made, such as Si / carbon composites. However, due to the complicated manufacturing process and low yield, it is not enough to commercialize it. Therefore, it is urgent to develop a lithium battery with comprehensive performance using silicon-based materials as negative electrode active materials. Summary of the invention
[0005] In order to improve the energy density of lithium batteries while achieving excellent rate performance and cycle performance, the present invention provides a negative electrode active material and application thereof.
[0006] In a first aspect, the present invention provides a negative electrode active material, which adopts the following technical solution:
[0007] A negative electrode active material comprising a carbon material and a silicon-based material;
[0008] The carbon material includes at least one of artificial graphite, natural graphite, soft carbon, hard carbon, mesophase carbon microspheres, and graphene;
[0009] The chemical formula of the silicon-based material is X a Si b Y c, wherein X includes at least one of P, As, Se, B, Ga, Mg, Al, Zn, and Li, Y includes at least one of O and C, and a, b, and c satisfy 0≤a≤8, 0≤c≤10, 1≤(a+b)≤10, and 2≤(b+c)≤10.
[0010] First, more lithium insertion sites are formed in the silicon-based material after being doped with the above elements, which helps to improve the energy density of the lithium battery. The silicon-based material in the present invention can greatly improve the energy density of the lithium battery after being mixed with the carbon material, and the battery energy density can be increased to 400Wh / kg at most; while the volume of the silicon-based material changes greatly during the lithium insertion process, the negative electrode active material in the present invention can be maintained within a reasonable volume expansion range. This is because, on the one hand, after the silicon-based material of the present invention is doped with the above elements, by controlling the numerical range of a, b, and c and satisfying the above inequality, the silicon-based material can have a stable lattice, greatly reducing the lattice expansion of the silicon-based material caused by lithium ion embedding, thereby improving the charge and discharge stability of the lithium battery and helping to improve the cycle performance of the lithium battery. On the other hand, the negative electrode active material of the present invention is also matched with a carbon material, and the carbon material has a small expansion. After being mixed with the silicon-based material, the overall expansion of the negative electrode active material can be reduced. Second, the doping element introduces a shallow donor energy level or acceptor energy level in silicon, which can be intuitively understood as adding a springboard between the valence band and the conduction band, helping electrons or holes to more easily jump from the valence band to the conduction band, thereby reducing the resistivity of the silicon-based material, which helps to further improve the cycle performance of lithium batteries using silicon-containing negative electrodes. Third, due to the hybridization of the atomic orbitals of the doping elements, the conductivity of the negative electrode active material can also be improved, reducing the influence of the silicon-based material on the overall conductivity of the negative electrode active material, which helps to improve the rate performance of the lithium battery. Fourth, when Y in the silicon-based material is O, the volume change of silicon can be limited by the framework of silicon oxide, thereby further improving the cycle stability of the silicon-based material; and when Y in the silicon-based material is C, since the carbon expansion is less than the silicon expansion, the volume change of the silicon-based material during the charge and discharge process can be alleviated, thereby improving the cycle stability of the silicon-based material. At the same time, since the carbon material has good conductivity, the conductivity of the silicon-based material can also be further improved. In summary, the silicon-containing negative electrode active material in the present invention can have excellent rate performance while having high energy density.
[0011] Preferably, a and c satisfy 0.1≤a≤8, 0.1≤c≤8.
[0012] Preferably, when X includes at least one of As, Se, B, and Ga, a, b, and c satisfy 1≤a≤4, 1≤c≤3, 1≤(a+b)≤7, and 2≤(b+c)≤8.
[0013] By further limiting the types of X to include As, Se, B, and Ga, it helps to improve the structural stability of silicon-based negative electrode materials and improve the rate performance of lithium batteries.
[0014] Preferably, when X includes at least one of P, Mg, Al, Zn and Li, a, b and c satisfy 2≤a≤6, 1≤c≤5, 1≤(a+b)≤9 and 2≤(b+c)≤6.
[0015] By further limiting the types of X to include P, Mg, Al, Zn, and Li, it is helpful to form more lithium insertion potentials in silicon-based materials, and it is also helpful to increase the energy density of lithium batteries to form more lithium insertion sites, thereby improving the energy density of materials. At the same time, due to the orbital hybridization of the atoms of the doped elements, the conductivity of the material is improved, and the rate performance is further improved.
[0016] Preferably, when Y in the silicon-based material is O, the silicon-based material is prepared by a method comprising the following steps: mechanically ball-milling silicon oxide to obtain silicon particles with a particle size of 50-500 nm, mixing the doping element powder with high-purity silicon by high-speed ball milling, and calcining at 900-1200° C. to obtain the silicon-based material;
[0017] When Y in the silicon-based material is C, the silicon-based material is prepared by a method comprising the following steps: subjecting high-purity silicon to mechanical ball milling to obtain silicon particles with a particle size of 50-500nm, mixing the doping element powder and the high-purity silicon by high-speed ball milling, and calcining at 900-1200°C to obtain the doped silicon material; then, the doped silicon material and the carbon coating agent are dispersed and mixed at high speed by a fusion machine, and calcined at 1000-1500°C to obtain the silicon-based material; wherein the carbon coating agent includes at least one of asphalt, heavy oil, and phenolic resin.
[0018] Preferably, when the carbon material includes at least one of artificial graphite and natural graphite, Y is O or C.
[0019] Since graphite material is an ordered layered material, its first coulombic efficiency is high, and its interlayer expansion is large during the charging and discharging process. By controlling Y to O or C, the silicon-based material and the graphite material are combined to reduce the first efficiency loss to a certain extent.
[0020] Preferably, when the carbon material includes at least one of soft carbon, hard carbon, mesocarbon microbeads, and graphene, Y is C.
[0021] Since soft carbon, hard carbon, mesophase carbon microspheres, and graphene have good disordered structures or porous structures and excellent rate performance, the energy density of the above carbon materials is relatively low; when Y is C, the above carbon materials are mixed with SiC materials to effectively improve the energy density of lithium batteries.
[0022] Preferably, when the carbon material comprises at least one of artificial graphite and natural graphite, the D50 of the carbon material is 5-18 μm, (D90-D10) / D50≤3, and the specific surface area is 0.5-3.0 m 2 / g.
[0023] Preferably, when the carbon material comprises at least one of soft carbon, hard carbon, mesophase carbon microspheres, and graphene, the carbon material has a D50 of 0.5-20 μm, 1≤(D90-D10) / D50≤5, and a specific surface area of 1.5-5.0 m 2 / g.
[0024] According to the expansion degree of carbon materials, carbon materials with appropriate particle sizes are selected to match with silicon-based negative electrode materials. The particle size distribution range of soft carbon, hard carbon, mesophase carbon microspheres, and graphene with small expansion degrees is relatively wide. Larger carbon material particles can form a relatively stable accommodation space between particles, providing a buffer area for the expansion of silicon-based materials, reducing the expansion and deformation degree of the negative electrode active material layer, and small particles of carbon materials can be distributed between silicon-based material particles to form a good conductive network, thereby improving the conductivity of the negative electrode active material layer. Therefore, by controlling the particle size D50, particle size concentration, and specific surface area of different types of carbon materials according to different types of carbon materials, the degree of coordination between carbon materials and silicon-based materials can be improved, forming a negative electrode active material layer with appropriate tortuosity, significantly improving the speed of lithium ion transmission at the negative electrode, avoiding the occurrence of lithium dendrites at the negative electrode, and improving the rate performance of lithium batteries while improving the cycle stability of lithium batteries.
[0025] Preferably, the D50 of the silicon-based material is 0.05-5 μm.
[0026] By selecting silicon-based materials with appropriate particle sizes, the particle size of the silicon-based materials is controlled within a smaller range, and the ion diffusion path is short, which helps to improve the rate performance of lithium batteries.
[0027] Preferably, the mass ratio of the carbon material to the silicon-based material is 20-98:0.5-30.
[0028] In a second aspect, the present invention provides a negative electrode sheet, which adopts the following technical solution:
[0029] A negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer arranged on the negative electrode current collector, wherein the negative electrode active material layer comprises the negative electrode active material according to any one of claims 1 to 9.
[0030] Preferably, the negative electrode active material layer also includes a conductive agent and a binder; the conductive agent includes at least one of Ketjen black, acetylene black, carbon fiber VGCF, and carbon nanotube CNT; the binder includes at least one of polyvinylidene fluoride PVDF, carboxymethyl cellulose CMC, and polyacrylic acid PAA.
[0031] Preferably, when the carbon material includes at least one of artificial graphite and natural graphite, the mass ratio of the carbon material, the silicon-based material, the conductive agent and the binder is 70-98: 0.5-25: 0.1-5: 0.1-6.0.
[0032] Preferably, when the carbon material includes at least one of soft carbon, hard carbon, mesophase carbon microbeads, and graphene, the mass ratio of the carbon material, the silicon-based material, the conductive agent, and the binder is 30-90: 0.5-30: 0.1-5: 0.1-6.0.
[0033] Preferably, the porosity of the negative electrode active material layer is 10%-70%.
[0034] Preferably, the ratio of D50 of the silicon-based material to the thickness of the negative electrode active material layer in the negative electrode sheet is 0.0002-0.8:1.
[0035] By controlling the ratio of the D50 of the silicon-based material to the thickness of the negative electrode active material layer, the expansion effect of the silicon-based active material during the cycle will not only not have a negative impact on the structural stability of the negative electrode active material layer, but the expansion of the silicon negative electrode active material will also produce a pore structure in the negative electrode active material layer that is convenient for ion transmission, thereby improving the ion transmission performance between the positive and negative electrodes, thereby improving the rate performance and cycle performance of the lithium battery.
[0036] Preferably, the surface density of the negative electrode sheet is 180-500 g / m 2 .
[0037] In a third aspect, the present invention provides a lithium battery, which adopts the following technical solution:
[0038] A lithium battery comprises a positive electrode sheet, a separator, an electrolyte and the negative electrode sheet as described above. DETAILED DESCRIPTION
[0039] For better understanding and implementation, the technical solution of the present invention will be clearly and completely described below in conjunction with embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments.
[0040] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0041] Unless otherwise indicated, all numerical values expressing quantities of ingredients, reaction conditions, and so forth used in the specification and claims are to be understood as modified by the term “about.” Accordingly, unless indicated to the contrary, the numerical parameters set forth herein are approximations that can vary depending upon the desired properties desired to be obtained.
[0042] As used herein, "and / or" means one or all of the mentioned elements.
[0043] As used herein, “including” and “comprising” encompasses the case where only the stated elements are present as well as the case where there are other elements other than the stated elements.
[0044] All percentages in the present invention are by weight, unless otherwise specified.
[0045] Unless otherwise indicated, "a", "an", "an" and "the" used in this specification are intended to include "at least one" or "one or more". For example, "a component" means one or more components, so more than one component may be considered and may be employed or used in the implementation of the embodiment.
[0046] Example 1
[0047] 1. Preparation of negative electrode active materials
[0048] The negative electrode active material includes a carbon material and a silicon-based material in a mass ratio of 70:5;
[0049] The carbon material is artificial graphite, the particle size D50 of the carbon material is 6 μm, (D90-D10) / D50=2.2, and the specific surface area is 2.8 m 2 / g;
[0050] The chemical formula of silicon-based materials is X a Si b Y c , X is As, Y is O, a=0.1, c=0.1, (a+b)=9, (b+c)=9; and the D50 of the silicon-based material is 0.2 μm.
[0051] 2. Negative electrode preparation
[0052] The negative electrode slurry was prepared as follows: the above-mentioned negative electrode active material (the mass ratio of carbon material and silicon-based material was 70:5), conductive agent acetylene black, thickener CMC, and binder SBR were added into a vacuum mixer at a mass ratio of 70:5:0.2:0.2 for mixing, and then deionized water was added as a solvent to the mixture obtained, and the mixed slurry was stirred until it was uniform under the action of the vacuum mixer, thereby obtaining the negative electrode slurry of this embodiment.
[0053] The negative electrode slurry is evenly coated on both surfaces of the negative electrode current collector copper foil, dried at room temperature and then transferred to an oven for further drying. After drying in the oven, a negative electrode sheet semi-finished product is obtained, and then the negative electrode sheet semi-finished product is cold pressed and cut to obtain the negative electrode sheet to be assembled.
[0054] 3. Preparation of positive electrode
[0055] The positive electrode slurry was prepared as follows: the positive electrode active material (lithium iron phosphate), the conductive agent acetylene black, and the binder PVDF were added into a vacuum mixer in a mass ratio of 97.9:0.9:1.2 for mixing, and then the solvent NMP was added into the mixed slurry, and the mixed slurry was stirred into a uniform state under the action of the vacuum mixer, thereby obtaining the positive electrode slurry of this embodiment.
[0056] The positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature and then transferred to an oven for further drying. After drying in the oven, a positive electrode sheet semi-finished product is obtained, and then the positive electrode sheet semi-finished product is cold pressed and cut to obtain the positive electrode sheet to be assembled.
[0057] 4. Lithium-ion battery assembly
[0058] A commercially available polyethylene film is used as a separator of a lithium-ion battery, and a commercially available electrolyte suitable for a battery with a voltage system of 3.65V (charging upper limit) is used as an electrolyte. The positive electrode sheet, the negative electrode sheet and the separator are wound together to obtain a bare cell, and the bare cell is packaged, injected, left to stand, formed, and divided to obtain a finished battery.
[0059] Example 2
[0060] 1. Preparation of negative electrode active materials
[0061] The negative electrode active material includes a carbon material and a silicon-based material in a mass ratio of 95:20;
[0062] The carbon material is natural graphite, the particle size D50 of the carbon material is 16 μm, (D90-D10) / D50=2.8, and the specific surface area is 0.8 m 2 / g;
[0063] The chemical formula of silicon-based materials is X a Si b Yc , X is P, Y is C, a=8, c=8, (a+b)=10, (b+c)=10; D50 of silicon-based material is 0.05-5μm.
[0064] 2. Negative electrode preparation
[0065] The negative electrode slurry was prepared as follows: the above-mentioned negative electrode active material (the mass ratio of carbon material and silicon-based material was 95:20), conductive agent acetylene black, thickener CMC, and binder SBR were added into a vacuum mixer in a mass ratio of 95:20:4.5:5.8 for mixing, and then deionized water was added as a solvent to the mixture obtained, and the mixed slurry was stirred until it was uniform under the action of the vacuum mixer, thereby obtaining the negative electrode slurry of this embodiment.
[0066] The negative electrode slurry is evenly coated on both surfaces of the negative electrode current collector copper foil, dried at room temperature and then transferred to an oven for further drying. After drying in the oven, a negative electrode sheet semi-finished product is obtained, and then the negative electrode sheet semi-finished product is cold pressed and cut to obtain the negative electrode sheet to be assembled.
[0067] 3. Preparation of positive electrode
[0068] The positive electrode slurry was prepared as follows: the positive electrode active material (lithium iron phosphate), the conductive agent acetylene black, and the binder PVDF were added into a vacuum mixer in a mass ratio of 97.9:0.9:1.2 for mixing, and then the solvent NMP was added into the mixed slurry, and the mixed slurry was stirred into a uniform state under the action of the vacuum mixer, thereby obtaining the positive electrode slurry of this embodiment.
[0069] The positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature and then transferred to an oven for further drying. After drying in the oven, a positive electrode sheet semi-finished product is obtained, and then the positive electrode sheet semi-finished product is cold pressed and cut to obtain the positive electrode sheet to be assembled.
[0070] 4. Lithium-ion battery assembly
[0071] A commercially available polyethylene film is used as a separator of a lithium-ion battery, and a commercially available electrolyte suitable for a battery with a voltage system of 3.65V (charging upper limit) is used as an electrolyte. The positive electrode sheet, the negative electrode sheet and the separator are wound together to obtain a bare cell, and the bare cell is packaged, injected, left to stand, formed, and divided to obtain a finished battery.
[0072] Example 3
[0073] 1. Preparation of negative electrode active materials
[0074] The negative electrode active material includes a carbon material and a silicon-based material in a mass ratio of 90:30;
[0075] The carbon material is hard carbon, the particle size D50 of the carbon material is 17 μm, (D90-D10) / D50=3, and the specific surface area is 1.5 m 2 / g;
[0076] The chemical formula of silicon-based materials is X a Si b Y c , X is Mg, Y is C, a=0.5, c=1.5, (a+b)=1, (b+c)=2; and the D50 of the silicon-based material is 5 μm.
[0077] 2. Negative electrode preparation
[0078] The negative electrode slurry was prepared as follows: the above-mentioned negative electrode active material (the mass ratio of carbon material and silicon-based material was 90:30), conductive agent acetylene black, thickener CMC, and binder SBR were added into a vacuum mixer in a mass ratio of 90:30:5:6 for mixing, and then deionized water was added as a solvent to the mixture obtained, and the mixed slurry was stirred until it was uniform under the action of the vacuum mixer, thereby obtaining the negative electrode slurry of this embodiment.
[0079] The negative electrode slurry is evenly coated on both surfaces of the negative electrode current collector copper foil, dried at room temperature and then transferred to an oven for further drying. After drying in the oven, a negative electrode sheet semi-finished product is obtained, and then the negative electrode sheet semi-finished product is cold pressed and cut to obtain the negative electrode sheet to be assembled.
[0080] 3. Preparation of positive electrode
[0081] The positive electrode slurry was prepared as follows: the positive electrode active material (lithium iron phosphate), the conductive agent acetylene black, and the binder PVDF were added into a vacuum mixer in a mass ratio of 97.9:0.9:1.2 for mixing, and then the solvent NMP was added into the mixed slurry, and the mixed slurry was stirred into a uniform state under the action of the vacuum mixer, thereby obtaining the positive electrode slurry of this embodiment.
[0082] The positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature and then transferred to an oven for further drying. After drying in the oven, a positive electrode sheet semi-finished product is obtained, and then the positive electrode sheet semi-finished product is cold pressed and cut to obtain the positive electrode sheet to be assembled.
[0083] 4. Lithium-ion battery assembly
[0084] A commercially available polyethylene film is used as a separator of a lithium-ion battery, and a commercially available electrolyte suitable for a battery with a voltage system of 3.65V (charging upper limit) is used as an electrolyte. The positive electrode sheet, the negative electrode sheet and the separator are wound together to obtain a bare cell, and the bare cell is packaged, injected, left to stand, formed, and divided to obtain a finished battery.
[0085] Example 4
[0086] 1. Preparation of negative electrode active materials
[0087] The negative electrode active material includes a carbon material and a silicon-based material in a mass ratio of 30:1;
[0088] The carbon material is soft carbon, the particle size D50 of the carbon material is 1.5 μm, (D90-D10) / D50=1, and the specific surface area is 5 m 2 / g;
[0089] The chemical formula of silicon-based materials is X a Si b Y c , X is Se, Y is C, a=1, c=1, (a+b)=2, (b+c)=2; and the D50 of the silicon-based material is 0.1 μm.
[0090] 2. Negative electrode preparation
[0091] The negative electrode slurry was prepared as follows: the above-mentioned negative electrode active material (the mass ratio of carbon material and silicon-based material was 30:1), conductive agent acetylene black, thickener CMC, and binder SBR were added into a vacuum mixer at a mass ratio of 30:1:0.1:0.1 for mixing, and then deionized water was added as a solvent to the mixture obtained, and the mixed slurry was stirred until it was uniform under the action of the vacuum mixer, thereby obtaining the negative electrode slurry of this embodiment.
[0092] The negative electrode slurry is evenly coated on both surfaces of the negative electrode current collector copper foil, dried at room temperature and then transferred to an oven for further drying. After drying in the oven, a negative electrode sheet semi-finished product is obtained, and then the negative electrode sheet semi-finished product is cold pressed and cut to obtain the negative electrode sheet to be assembled.
[0093] 3. Preparation of positive electrode
[0094] The positive electrode slurry was prepared as follows: the positive electrode active material (lithium iron phosphate), the conductive agent acetylene black, and the binder PVDF were added into a vacuum mixer in a mass ratio of 97.9:0.9:1.2 for mixing, and then the solvent NMP was added into the mixed slurry, and the mixed slurry was stirred into a uniform state under the action of the vacuum mixer, thereby obtaining the positive electrode slurry of this embodiment.
[0095] The positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil, dried at room temperature and then transferred to an oven for further drying. After drying in the oven, a positive electrode sheet semi-finished product is obtained, and then the positive electrode sheet semi-finished product is cold pressed and cut to obtain the positive electrode sheet to be assembled.
[0096] 4. Lithium-ion battery assembly
[0097] A commercially available polyethylene film is used as a separator of a lithium-ion battery, and a commercially available electrolyte suitable for a 3.651 SeV (charging upper limit) voltage system battery is used as an electrolyte. The positive electrode sheet, the negative electrode sheet and the separator are wound together to obtain a bare cell, and the bare cell is packaged, injected, left to stand, formed, and divided to obtain a finished battery.
[0098] Example 5
[0099] The difference between this embodiment and embodiment 1 lies in the preparation of the negative electrode active material, specifically:
[0100] The negative electrode active material includes a carbon material and a silicon-based material in a mass ratio of 70:5;
[0101] The carbon material is artificial graphite, the particle size D50 of the carbon material is 6 μm, (D90-D10) / D50=2.2, and the specific surface area is 2.8 m 2 / g;
[0102] The chemical formula of silicon-based materials is X a Si b Y c , X is As, Y is O, a=1, c=3, (a+b)=6, (b+c)=8; and the D50 of the silicon-based material is 0.2 μm.
[0103] The other steps and parameter settings are consistent with those in Example 1.
[0104] Example 6
[0105] The difference between this embodiment and embodiment 1 lies in the preparation of the negative electrode active material, specifically:
[0106] The negative electrode active material includes a carbon material and a silicon-based material in a mass ratio of 70:5;
[0107] The carbon material is artificial graphite, the particle size D50 of the carbon material is 6 μm, (D90-D10) / D50=2.2, and the specific surface area is 2.8 m 2 / g;
[0108] The chemical formula of silicon-based materials is X a Si b Y c , X is As, Y is O, a=1, c=2, (a+b)=7, (b+c)=8; and the D50 of the silicon-based material is 0.2 μm.
[0109] The other steps and parameter settings are consistent with those in Example 1.
[0110] Example 7
[0111] The difference between this embodiment and embodiment 3 lies in the preparation of the negative electrode active material, specifically:
[0112] The negative electrode active material includes a carbon material and a silicon-based material in a mass ratio of 90:30;
[0113] The carbon material is soft carbon, the particle size D50 of the carbon material is 1.5 μm, (D90-D10) / D50=1, and the specific surface area is 5 m 2 / g;
[0114] The chemical formula of silicon-based materials is X a Si b Y c , X is Mg, Y is C, a=5, c=2, (a+b)=9, (b+c)=6; and the D50 of the silicon-based material is 0.1 μm.
[0115] The other steps and parameter settings are consistent with those in Example 3.
[0116] Example 8
[0117] The difference between this embodiment and embodiment 3 lies in the preparation of the negative electrode active material, specifically:
[0118] The negative electrode active material includes a carbon material and a silicon-based material in a mass ratio of 90:30;
[0119] The carbon material is soft carbon, the particle size D50 of the carbon material is 1.5 μm, (D90-D10) / D50=1, and the specific surface area is 5 m 2 / g;
[0120] The chemical formula of silicon-based materials is X a Si b Y c , X is Mg, Y is C, a=2, c=1, (a+b)=3, (b+c)=2; and the D50 of the silicon-based material is 0.1 μm.
[0121] The other steps and parameter settings are consistent with those in Example 3.
[0122] Example 9
[0123] The difference between this embodiment and embodiment 1 is that D50 is 1.5 μm, (D90-D10) / D50=1, and the specific surface area is 5 m 2 The other steps and parameter settings are consistent with those in Example 1.
[0124] Example 10
[0125] The difference between this embodiment and embodiment 3 is that Y in the silicon-based material is O. Other steps and parameter settings are consistent with those in embodiment 3.
[0126] Embodiment 11
[0127] The difference between this embodiment and embodiment 3 is that the particle size D50 of the carbon material is 6 μm, (D90-D10) / D50=0.5, and the specific surface area is 1.2 m 2 The other steps and parameter settings are consistent with those in Example 3.
[0128] Example 12
[0129] The difference between this embodiment and embodiment 1 is that the ratio of D50 of the silicon-based material to the total thickness of the negative electrode active material layer in the negative electrode sheet is 0.9: 1. Other steps and parameter settings are consistent with those in embodiment 1.
[0130] Example 13
[0131] The difference between this embodiment and embodiment 1 is that the ratio of D50 of the silicon-based material to the total thickness of the negative electrode active material layer in the negative electrode sheet is 0.0001: 1. Other steps and parameter settings are consistent with those in embodiment 1.
[0132] Comparative Example 1
[0133] The difference between this comparative example and Example 1 is that the silicon-based material is not doped with X. Other steps and parameter settings are consistent with those in Example 1.
[0134] Comparative Example 2
[0135] The difference between this comparative example and Example 1 is that, in the silicon-based material, a=4, c=5, (a+b)=11, (b+c)=12. The other steps and parameter settings are consistent with those in Example 1.
[0136] Test Method
[0137] 1. Pole sheet surface density test
[0138] The negative electrode sheets in the above embodiments and comparative examples were tested for surface density. The specific test method was as follows: an anode of standard area (S) was taken, dried, and weighed by an electronic balance to obtain a weight of m, and its surface density was m / S.
[0139] 2. Coating porosity test
[0140] The porosity test was performed on the negative electrode active material layer on the negative electrode sheet in the above embodiments and comparative examples. The specific test method is: take a certain amount of electrode sheets, bake them in a vacuum drying oven for 8 hours at a baking temperature of 70°C, place the baked electrode sheets in a mercury intrusion instrument, set the pressure to 200 MPa, and calculate the porosity through the pore volume under different external pressures.
[0141] 3. Pole expansion rate test
[0142] The first full charge expansion rate test was carried out on the negative electrode active material layer on the negative electrode sheet in the above-mentioned embodiments and comparative examples. The specific test method is: record the initial thickness of the negative electrode sheet, recorded as d0; place the lithium battery in an environment of 25°C, use a 0.5C current to fully charge the battery, then disassemble the battery and test the anode thickness, recorded as d1; the first full charge expansion rate of the negative electrode sheet = (d1-d0) / d0×100%.
[0143] 4. Energy density test
[0144] The energy density test was performed on the lithium batteries in the above embodiments and comparative examples. The specific test method was as follows: weigh the weight of the test battery, recorded as m; place the battery in a fixture, apply a force of 3000N, charge the single battery to 3.65V at a constant current of 0.5C, leave it for 30min, discharge it to 2.5V at a constant current of 0.5C, leave it for 30min, and cycle it for 3 consecutive times; calculate the energy E (the average value of three cycles), and the discharge energy density = E / m (in Wh / kg).
[0145] 5. Cycle performance test
[0146] The lithium batteries in the above embodiments and comparative examples were subjected to cycle performance tests. The specific test method was as follows: at 25° C. and with a voltage range of 2.5-3.65 V, the prepared batteries were subjected to a charge and discharge cycle test at a current of 1 C for 1000 cycles, and the cycle capacity retention rate was recorded.
[0147] 6. Rate performance test
[0148] The lithium batteries in the above embodiments and comparative examples were subjected to rate performance tests. The specific test method was as follows: at 25°C and a voltage range of 2.5-3.65V, the prepared batteries were charged at a constant current and constant voltage of 3C current, with a cut-off voltage of 3.65V, the constant current charging capacity was recorded as C0, the total charging capacity was C1, and the 3C charging constant current ratio = C0 / C1×100%.
[0149] Table 1
[0150]
[0151] In combination with Examples 1-4, Comparative Examples 1-2 and Table 1, it can be seen that the carbon material of the present invention is matched with a silicon-based material, and a carbon material with a suitable particle size is selected according to different types of carbon materials to match with the silicon-based material, and a suitable element is doped in the silicon-based material. More lithium insertion sites are formed in the silicon-based material after doping with the above elements, which helps to improve the energy density of the lithium battery. The battery energy density can be increased to 400Wh / kg at most; and the element-doped silicon-based material has a more stable lattice structure, and when combined with the carbon material with weak expansion performance itself, the negative electrode active material in the present invention can be controlled within a reasonable volume expansion range. At the same time, the doped element can reduce the resistivity of the silicon-based material, which helps to improve the cycle performance and rate performance of the lithium battery.
[0152] Combining Examples 1, 5-6, 3, 7-8 and Table 1, it can be seen that further adjusting the values of a, b, and c in the silicon-based material according to the different doping elements in the silicon-based material can further improve the rate performance and cycle performance of the lithium battery.
[0153] In combination with Example 1, Example 9 and Table 1, it can be seen that when the doping elements in the silicon-based material do not match the value limits of a, b, and c, it will affect the structural stability of the silicon-based material to a certain extent, and is not conducive to improving the conductivity of the silicon-based material, which will affect the cycle performance and rate performance of the lithium battery to a certain extent.
[0154] In combination with Example 3, Examples 10-11 and Table 1, it can be seen that when the carbon material is artificial graphite, but its particle size parameter does not meet the specified range, or when the carbon material is hard carbon, but its particle size parameter does not meet the specified range, the cycle performance of the lithium battery decreases. This is because the silicon-based material cannot form a good matching effect with the carbon material at this time, which is not conducive to the formation of a negative electrode active material layer with a suitable pore structure, which will be unfavorable for improving the cycle performance of the lithium battery.
[0155] In combination with Example 3, Examples 12-13 and Table 1, it can be seen that when the ratio of the D50 of the silicon-based material to the total thickness of the negative electrode active material layer is too large, the expansion of the silicon negative electrode active material will affect the structural stability of the pore structure in the negative electrode active material layer. In severe cases, the negative electrode active material layer may even be deformed and cracked, which will affect the cycle performance of the lithium battery; when the ratio of the D50 of the silicon-based material to the total thickness of the negative electrode active material layer is too small, it is not conducive to the formation of a pore structure in the negative electrode active material layer that is convenient for the transmission of lithium ions and electrons, which affects the ion transmission performance between the positive and negative electrodes, and is further not conducive to the improvement of the rate performance and cycle performance of the lithium battery.
[0156] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solutions of the present invention can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present invention.
Claims
1. A negative electrode active material, characterized in that: Including carbon materials and silicon-based materials; The carbon material includes at least one of artificial graphite, natural graphite, soft carbon, hard carbon, mesophase carbon microspheres, and graphene; The chemical formula of the silicon-based material is X a Si b Y c , wherein X includes at least one of P, As, Se, B, Ga, Mg, Al, Zn, and Li, Y includes at least one of O and C, and a, b, and c satisfy 0≤a≤8, 0≤c≤10, 1≤(a+b)≤10, and 2≤(b+c)≤10.
2. The negative electrode active material according to claim 1, characterized in that: a and c satisfy 0.1≤a≤8 and 0.1≤c≤8.
3. The negative electrode active material according to claim 1, characterized in that: When X includes at least one of As, Se, B, and Ga, a, b, and c satisfy 1≤a≤4, 1≤c≤3, 1≤(a+b)≤7, and 2≤(b+c)≤8.
4. The negative electrode active material according to claim 1, characterized in that: When X includes at least one of P, Mg, Al, Zn, and Li, a, b, and c satisfy 2≤a≤6, 1≤c≤5, 1≤(a+b)≤9, and 2≤(b+c)≤6.
5. The negative electrode active material according to claim 1, characterized in that: When the carbon material includes at least one of artificial graphite and natural graphite, Y is 0 or C.
6. The negative electrode active material according to claim 1, characterized in that: When the carbon material includes at least one of soft carbon, hard carbon, mesocarbon microbeads, and graphene, Y is C.
7. The negative electrode active material according to claim 5, characterized in that: When the carbon material comprises at least one of artificial graphite and natural graphite, the carbon material has a D50 of 5-18 μm, (D90-D10) / D50≤3, and a specific surface area of 0.5-3.0 m 2 / g.
8. The negative electrode active material according to claim 6, characterized in that: When the carbon material includes at least one of soft carbon, hard carbon, mesophase carbon microspheres, and graphene, the D50 of the carbon material is 0.5-20 μm, 1≤(D90-D10) / D50≤5, and the specific surface area is 1.5-5.0 m 2 / g.
9. The negative electrode active material according to claim 1, characterized in that: The D50 of the silicon-based material is 0.05-5 μm.
10. The negative electrode active material according to any one of claims 1 to 9, characterized in that: The mass ratio of the carbon material to the silicon-based material is 20-98:0.5-30.
11. A negative electrode sheet, characterized in that: The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector, wherein the negative electrode active material layer comprises the negative electrode active material according to any one of claims 1 to 10.
12. The negative electrode sheet according to claim 11, characterized in that: The porosity of the negative electrode active material layer is 10%-70%.
13. The negative electrode sheet according to claim 11, characterized in that: The ratio of D50 of the silicon-based material to the thickness of the negative electrode active material layer in the negative electrode sheet is 0.0002-0.8:
1.
14. The negative electrode sheet according to claim 11, characterized in that: The surface density of the negative electrode sheet is 180-500g / m 2 .
15. A lithium battery, characterized in that: The invention comprises a positive electrode sheet, a separator, an electrolyte and a negative electrode sheet as claimed in any one of claims 11 to 14.
Citation Information
Patent Citations
Element-doped SiOx negative electrode composite material as well as preparation method and application thereof
CN106654194A
Anode active material for lithium secondary battery, anode comprising the same for lithium secondary battery and lithium secondary battery comprising the anode
CN110892566A
Lithium ion battery of silicon negative electrode system
CN113745646A
Negative pole piece, secondary battery and device comprising secondary battery
CN116435517A
High-first-efficiency and high-rate silicon-based negative electrode material and preparation method therefor
WO2022257311A1
Cited By
Negative electrode active material and use thereof
WO2026097729A1